Effect of TiO2 Nanoparticles on Poly(methyl methacrylate) Based Solid Polymer Electrolyte System for Battery Characterization Studies - Ch, P.; Sekhar*, ra; Naveen Kumar, P.; Sasikala, U.; Sharma, A.K. (Asian Journal of Chemistry, 2013)
Solid polymer electrolyte films of poly(methyl methacrylate) (PMMA) with NaClO4, NaClO4 + plasticizer (DMF) and NaClO4 + DMF + TiO2 nanoparticles have been prepared by solution cast technique. The features of complexation of the electrolytes were studied by X-ray diffraction. DC conductivity of the films was measured in the temperature range 303-393 K. The variation of ionic conductivity as a function of temperature was analyzed. In the temperature range studied, three regions with different activation energies were observed. Transference number data showed that the charge transport in this system is predominantly due to ions only. Electrochemical cells of configuration Na/(PMMA + NaClO4 + DMF + TiO2)/(I2 + C + electrolyte) were fabricated and the discharge characteristics of these cells were studied under a constant load of 100 kW. The nano composite polymer electrolyte system showed an increased discharge time with respect to plasticized PMMA + NaClO4 electrolyte system.